Answer:
- y = -3/8(x - 4)² + 7 or y = -3/8x² + 6x + 1
Step-by-step explanation:
We can see on the graph that the vertex is (4, 7) and the leading coefficient is negative as parabola opens down.
The vertex form is:
- y = a(x - h)² + k, substitute coordinates to get,
- y = a(x - 4)² + 7
Considering the y-intercept is (0, 1), substitute values to find the value of a:
- 1 = a(0 - 4)² + 7
- a(4²) = 1 - 7
- 16a = -6
- a = -6/16
- a = -8/3
The function is:
In standard form:
- y = -3/8(x² - 16x + 16) + 7 = -3/8x² + 6x - 6 + 7 = -3/8x² + 6x + 1